Pengembangan Video Tutorial Penataan Modifikasi Hijab Pengantin Akad Nikah - Fatimah Nabila; Jenny Sista Siregar; Aniesa Puspa Arum (Journal on Education, 2024)
Limited time and learning media in bridal hijab styling material in the Cosmetology Education Study Program creates difficulties in the learning process. From the results of the needs analysis, 100% of respondents agreed that a video tutorial on how to modify the bridal hijab for their wedding ceremony was carried out. This research focuses on developing learning media, namely by producing video tutorials which makes this research included in the Research and Development (R&D) type of research using the ADDIE development model, but is limited to the development stage. The aim of this research is to develop video tutorials so that they can serve as information and references for students and the general public to improve their skills in arranging bridal hijab modifications. The data analysis technique uses a mix method, namely data collection and analysis is carried out using quantitative and qualitative research. This development research was carried out through a validation test process by material experts and media experts, as well as student practicality tests. In the material expert assessment I at stage I it was 67.69% and at stage II it was 86.15%. Then, the results of the material expert validation test II were 96.92% so it was included in the "Very Eligible" category. Meanwhile, the score obtained from the media expert validation test in stage I was 92% and in stage II it was 97.33%, so it was included in the "Very Eligible" category. At the practicality test stage carried out on 2020 and 2021 UNJ Cosmetology Education students, there were One to One trial results of 97.43% and Small Group trials of 91.07% which fell into the "Very Practical" category. Thus, video tutorials for arranging modifications to the bridal hijab at the wedding ceremony can be used as a learning medium.